Unheard and unused: why students reject teacher and peer feedback - Lipnevich, Anastasiya A.; Lopera-Oquendo, Carolina; Tomazin, Ligia; Gutterman, Jonathan; Florentin, Carmen (Frontiers in Education, 2025)
BackgroundIn higher education, feedback has become a significant focus of study over the years. Despite established high-quality feedback criteria, the issue of students not utilizing feedback from instructors and peers persists. This study identifies key barriers to feedback utilization and offers insights that can inform more responsive and student-centered feedback practices.AimsThis study investigated specific reasons behind feedback rejections in higher education and how individual characteristics (college students' gender, ethnicity, and academic level) predicted the reasons to reject teacher and peer feedback.MethodsUndergraduate and graduate students (N = 200, 67.7% women) from various colleges within a large public university in the northeast of the USA were asked to describe possible reasons why they did not use feedback provided by their instructors and peers' feedback on an academic assignment. Students' responses were analyzed using a deductive approach with a coding system based on the Student-Feedback Interaction Framework.ResultsStudents tend not to use or reject teacher feedback due to ambiguous or unclear messages, negative tone, lack of respect or trust in the teacher, and confidence in their performance. Peer feedback is commonly rejected because of a perceived lack of peer expertise, ambiguous messages, and negative emotional responses. Multiple logistic regressions found that gender and educational level are significant predictors of reasons for not utilizing feedback, with distinct patterns observed among male students and undergraduates.ConclusionThis study underscores the need for feedback strategies addressing individual student characteristics and contextual factors. Recommendations include fostering positive teacher-student relationships, enhancing the clarity of feedback, and improving students' skills in peer feedback provision and utilization.